Students, lecturers, graduates of the Minsk Law Institute – participants of the Great Patriotic War (to the 80th anniversary of Great Victory) - Shidlovsky, Andrey V.; Golubeva, Lyudmila L.; Dovnar, Taisiya I. (Journal of the Belarusian State University. Law, 2025)
The article is devoted to the study of the contribution of students, graduates, and lecturers of the Minsk Law Institute to the fight against the nazi invaders and to achieving the Great Victory. The article shows the key role of famous doctors of law, professors of the faculty of law of the Belarusian State University, participants of the Great Patriotic War in the formation and development of legal science and education in Belarus.